Suppression of References to Sex and Body Functions in the Brazilian and Portuguese Translations of J.D. Salinger's The Catcher in the Rye - Schmitz, John (Meta, 1998)
AbstractIn this comparison of two translations into Portuguese, one Brazilian, the other European, of Salinger's The Catcher in the Rye, an instant success in the United States from its publication in 1951, the author points out translational deviations and freedoms in the translated renditions of this work and stresses the need for translators to be faithful to the original text and not censure the language by "erasing" what they find objectionable.